Cranio-vertebral transition assessment by magnetic resonance imaging in a sample of a northeast Brazilian population - Heitor Cabral Frade; Caio César Nuto Leite França; José Jailson Costa do Nascimento; Maurus Marques de Almeida Holanda; Eulâmpio José da Silva Neto; Severino Aires Araújo Neto (Arquivos de Neuro-Psiquiatria)
ABSTRACT Platybasia and basilar invagination are important alterations of the cranial-vertebral transition. Neuroimaging-based platybasia parameters include the Welcker basal angle, distance between the apex of the odontoid and Chamberlain’s line, and the clivus-canal angle. This study aimed to measure and correlate these parameters in a sample from northeast Brazil. Methods Cross-sectional analysis of craniometric parameters from individuals submitted to magnetic resonance at an outpatient imaging center between 2011 and 2012. Results Of 181 analyzed cases, the Welcker basal angle averaged 128.96º (SD 6.51), median distance between apex of the odontoid and Chamberlain’s line was 2.27 mm (IQR -1.23–4.47) and the median clivus-canal angle was 150.5º (IQR 143.2–157.3). The Welcker basal angle was inversely correlated to the clivus-canal angle, and correlated to the distance between the apex of the odontoid and Chamberlain’s line. Conclusion There was a tendency to platibasia, basilar invagination and narrowing of the cranio-vertebral transition.